Regional variation in long-term population trends for the Greater White-fronted Goose Anser albifrons in Japan - Shimada, Tetsuo; Mori, Akira; Tajiri, Hironobu (Wildfowl, 2019)
Japan has the largest population of Greater White-fronted Geese Anser albifrons wintering in eastern Asia. The effective conservation of this East Asia goose population requires an understanding of their status and distribution in Japan. Long-term (15-year) trends in numbers were analysed from four main wintering areas â€“ northern Miyagi, Kaetsu, Hokuriku and Sanin â€“ in relation to nationwide trends recorded for Greater White-fronted Geese in Japan. Annual trend indices over 5-year (2013/14â€“2017/18), 10-year (2008/09â€“2017/18) and 15-year (2003/04â€“2017/18) periods were calculated using TRIM software. These indices showed a significant increase both for Japan nationally and for northern Miyagi over the 15-year timescale, with moderate declines in Hokuriku and uncertain trends for Kaetsu and Sanin. Analysis of more recent, shorter-term trends found that numbers in Japan and in northern Miyagi have undergone a â€œmoderate or strong increaseâ€ over the past 5 and 10 years. Conversely, goose trends showed â€œmoderate declinesâ€ in Sanin and Hokuriku over the past 10 years. Despite a significant positive correlation between trends recorded for the whole of Japan and those for northern Miyagi, there were no significant correlations with the other regions. There was no evidence for weather conditions, notably air temperature and snow depth, having an effect on numbers of geese in Miyagi and Kaetsu. Snow depth and air temperature, however, had a negative effect on numbers in Hokuriku and Sanin, respectively. In addition to the winter trends analyses, data from satellite tracking and recovery data from marked geese suggested that difference in the trends recorded between geese in northern (northern Miyagi) and those in southwestern Japan (Hokuriku and Sanin) could be explained by differences in migration routes taken by geese wintering in northern and southwestern Japan.